1999
DOI: 10.1046/j.1420-9101.1999.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression in Campanula rapunculoides L. I. A comparison of inbreeding depression in plants derived from strong and weak self-incompatibility phenotypes

Abstract: The evolution of selfing taxa from outcrossing ancestors has occurred repeatedly and is the subject of many theoretical models, yet few empirical studies have examined the immediate consequences of inbreeding in a population with variable expression of self‐incompatibility. Because self‐incompatibility breaks down with floral age in Campanula rapunculoides, we were able to mate outbred and selfed maternal plants in a crossing design which produced progeny with inbreeding coefficients of 0, 0.25, 0.50 and 0.75.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 68 publications
8
72
0
Order By: Relevance
“…Vogler et al (1999) found that individuals of Campanula ranunculoides with weak self-incompatibility reactions showed lower loss of fitness upon selfing than did individuals with strong selfincompatibility reactions. There may have been purging of highly deleterious alleles in the lines with the leaky selfincompatibility.…”
Section: Discussionmentioning
confidence: 95%
“…Vogler et al (1999) found that individuals of Campanula ranunculoides with weak self-incompatibility reactions showed lower loss of fitness upon selfing than did individuals with strong selfincompatibility reactions. There may have been purging of highly deleterious alleles in the lines with the leaky selfincompatibility.…”
Section: Discussionmentioning
confidence: 95%
“…The phenotype of an individual may depend not only on its own inbreeding coefficient, but also on that of its mother (Vogler et al 1999). The maternal inbreeding effect can be estimated by comparing plants from reciprocal crosses in which the parents differ in their respective inbreeding coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study of Gilia achilleifolia appears to demonstrate that such associations exist; highly herkogamous individuals showed more severe inbreeding depression than individuals with low anther-stigma separation (Takebayashi and Delph, 2000). Several other studies have also found similar correlations between family-level inbreeding depression and traits that influence outcrossing rate (Vogler et al, 1999;Stone and Motten, 2002). However, a multilocus simulation study suggested that genetic associations are unlikely to be observed (Schultz and Willis, 1995).…”
Section: Introductionmentioning
confidence: 95%